2016
DOI: 10.1093/nar/gkw190
|View full text |Cite
|
Sign up to set email alerts
|

G-register exchange dynamics in guanine quadruplexes

Abstract: G-quadruplexes (GQs) are 4-stranded DNA structures formed by tracts of stacked, Hoogsteen-hydrogen bonded guanosines. GQs are found in gene promoters and telomeres where they regulate gene transcription and telomere elongation. Though GQ structures are well-characterized, many aspects of their conformational dynamics are poorly understood. For example, when there are surplus guanosines in some of the tracts, they can slide with respect to one another, a process we term G-register (GR) exchange. These motions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 85 publications
3
66
0
Order By: Relevance
“…From our analysis of the human mtDNA sequences, there is clear evidence that CSB 2 varies in the number of residues in both the first and second G-runs, although >84% of the changes are in the second G-run of a G6AG n sequence, where N = 2–11 (Figure 2 ). As the total number of guanine residues was increased, there was a general trend towards increased transcription termination measured in vitro (Figure 2 ), as one would predict from an increase in quadruplex stability as more tetrads form ( 52 )). However, regardless of the variant investigated in vitro , the 3′ ends of the terminated transcripts were located at similar downstream sequences (Figure 5 ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…From our analysis of the human mtDNA sequences, there is clear evidence that CSB 2 varies in the number of residues in both the first and second G-runs, although >84% of the changes are in the second G-run of a G6AG n sequence, where N = 2–11 (Figure 2 ). As the total number of guanine residues was increased, there was a general trend towards increased transcription termination measured in vitro (Figure 2 ), as one would predict from an increase in quadruplex stability as more tetrads form ( 52 )). However, regardless of the variant investigated in vitro , the 3′ ends of the terminated transcripts were located at similar downstream sequences (Figure 5 ).…”
Section: Discussionmentioning
confidence: 78%
“…The quantified data and statistical variation are shown in Supplementary Figure S6. There was a general trend towards increased TP levels as the as the total length of the G-tract was increased, as one would predict from an increase in quadruplex stability as more guanine tetrads can form ( 52 ). In most cases only TP1 and TP2 bands were visible above background (Supplementary Figure S6B–D).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…With another long repeat sequence, the double G-to- I substituted TAG 3 (TTAG 3 ) 7 TT, it was found that one permutation of -substitutions at the 5′-end produced a minor increase in the thermodynamic stability relative to the wild type, while four other double mutations, however, decreased it, some of them significantly [ 331 ]. G-to-I substitutions were also used with GQs of A(htel-21) and A(htel-21)T [ 332 ], the VEGFA G 3 AG 3 TTG 4 TG 3 , the c-myc Pu18 AG 3 TG 4 AG 3 TG 4 , and the PIM1 G 3 CG 4 CG 5 CG 4 sequences [ 333 ]. Guanine in the central TGT loop of the TBA GQ was replaced by adenine or hypoxanthine to study the role of G8 in the GQ stabilization.…”
Section: Natural Base Lesions and Epigenetic Modifications In Gq Dmentioning
confidence: 99%
“…It is interesting that "excess" of guanosines in some G tracts can cause their sliding relative to each other during formation of quadruplex structures. It was shown that this process stabilized the folded state; the T m value of G4 increased significantly due to favorable entropic changes [136].…”
Section: Methods Used For G4 Analysis In Vitro;mentioning
confidence: 97%